Fractional CO2 Laser for Treatment of Vulvovaginal Atrophy: A Short Time Follow-up - Zinat Ghanbari; Samira Sohbati; Tahereh Eftekhar; Leyla Sahebi; Soodabeh Darvish; Safa Alasiri; Maryam Deldar Pasikhani (Tehran University of Medical Sciences, 2020)
Objective: The aim of this study was to evaluate the safety and efficacy of fractional CO2 laser for treatment of vulvovaginal atrophy. Materials and methods: In this clinical trial study, we evaluated the laser effect on vulvovaginal atrophy in 47 women aged 43-80 years. Each woman was treated with fractional CO2 laser, SmartXide2V2LR, DEKA, Monalisa Touch, vaginal 360o probe and cosmetic probe. The severity of vulvovaginal atrophy symptoms was evaluated before first session of laser and every 4 weeks after laser treatment until 12 weeks. Adverse effects including pain and itching were assessed at all visits. The statistical analysis was performed using SPSS version 23. Results: The response to laser therapy for vaginal dryness was significantly (p <0.001) improved. Also, the response to laser therapy for each symptom include dyspareunia, vaginal discharge, itching and urge urinary incontinence was statistically significant (p <0.001) based on visual analogue scale (VAS). Conclusion: It seems vaginal fractional CO2 laser can be applied as an effective and safe treatment method in genitourinary syndrome of menopause (GSM). It is necessary to conduct studies with long-term follow-up.